The global environmental injustice of fast fashion - Rachel Bick; Erika Halsey; Christine C. Ekenga (BMC, 2018)
Abstract Fast fashion, inexpensive and widely available of-the-moment garments, has changed the way people buy and dispose of clothing. By selling large quantities of clothing at cheap prices, fast fashion has emerged as a dominant business model, causing garment consumption to skyrocket. While this transition is sometimes heralded as the "democratization" of fashion in which the latest styles are available to all classes of consumers, the human and environmental health risks associated with inexpensive clothing are hidden throughout the lifecycle of each garment. From the growth of water-intensive cotton, to the release of untreated dyes into local water sources, to worker's low wages and poor working conditions; the environmental and social costs involved in textile manufacturing are widespread. In this paper, we posit that negative externalities at each step of the fast fashion supply chain have created a global environmental justice dilemma. While fast fashion offers consumers an opportunity to buy more clothes for less, those who work in or live near textile manufacturing facilities bear a disproportionate burden of environmental health hazards. Furthermore, increased consumption patterns have also created millions of tons of textile waste in landfills and unregulated settings. This is particularly applicable to low and middle-income countries (LMICs) as much of this waste ends up in second-hand clothing markets. These LMICs often lack the supports and resources necessary to develop and enforce environmental and occupational safeguards to protect human health. We discuss the role of industry, policymakers, consumers, and scientists in promoting sustainable production and ethical consumption in an equitable manner.